Axial Compressive Loading Attenuates Early Osteoarthritis by Reducing Subchondral Bone Remodeling. Issue 7 (June 2023) - Wu, Jianqun; Pan, Yonghao; Yu, Yangyi; Yang, Qihao; Liu, Qisong; Liu, Yang; Zhong, Jinhao; Fu, Linhao; Cai, Haotian; Liu, Chao; Li, Guangheng
Background: Mechanical loading and alendronate (ALN) can be used as noninvasive physical therapy methods for osteoarthritis (OA). However, the timing and efficacy for treatments are unknown. Purpose: To determine whether the timing of mechanical loading and ALN influences the pathobiological changes of OA. Study Design: Controlled laboratory study. Methods: Mice with OA induced by anterior cruciate ligament transection were subjected to early (1-3 weeks) or late (5-7 weeks) axial compressive dynamic load or intraperitoneal injection of ALN. Changes in gait were analyzed using gait analysis system, pathobiological changes in subchondral bone, cartilage, osteophyte, and synovitis were assessed using micro–computed tomography, tartrate-resistant acid phosphatase staining, pathologic section staining, and immunohistochemistry at 1, 2, 4, and 8 weeks. Results: At 1, 2, and 4 weeks, the OA limb had lower mean footprint pressure intensity, lower bone volume per tissue volume (BV/TV) in the subchondral bone, and more osteoclasts. At 4 weeks, the early loading, ALN, and load + ALN treatments induced less cartilage destruction, with a corresponding reduction in Osteoarthritis Research Society International score and increased hyaline cartilage thickness. The treatments also resulted in fewer osteoclasts and higher BV/TV and bone mineral density of subchondral bone and suppressed inflammation and interleukin 1β– and tumor necrosis factor α-positive cells in synovium. At 8 weeks, early loading or load + ALN improved the mean footprint pressure intensity and knee flexion. At 8 weeks, early load + ALN had a synergistic effect on protecting hyaline cartilage and proteoglycans. Footprint pressure intensity and cartilage destruction were worse in late loading limbs, and no differences in BV/TV, bone mineral density, osteophyte formation, and synovium inflammation were found between the late load, ALN, and load + ALN groups and the anterior cruciate ligament transection group. Conclusion: Dynamic axial mechanical loading or ALN in the early stages of knee trauma protected against OA by suppressing subchondral bone remodeling. However, late loading promoted cartilage degeneration in advanced OA, indicating that reduced loading should be performed in the late stages of OA to avoid the acceleration of OA. Clinical Relevance: Early low-level functional exercise or antiosteoporotic drugs could clearly slow or prevent the progression of early OA. For patients with mild to severe OA, loading reduction via brace protection or maintenance of joint stability via early ligament reconstruction surgery may ameliorate OA exacerbation.